Sound production in an Australian cockroach, Megazosteria patula (Walker) (Blattodea: Blattidae: Polyzosteriinae) - Rentz, David (Zootaxa, 2017)
The large, diurnal Australian cockroach, Megazosteria patula (Walker), produces a sound when disturbed. The sound was found to be a form of stridulation caused by the rubbing of pegs on the underside of the thoracic segments against a ridge on the following segment.